Hubungan Konsentrasi Timbal dalam Darah dengan C-Reactive Protein (CRP) dalam Plasma Manusia Silver - Balqis , Alifa Tiara; Dhanti , Kurnia Ritma; Djalil, Asmiyenti Djaliasrin; Sulistiyowati, Retno (Lontara Journal of Health Science and Technology, 2026)
Silver humansrefer to individuals who cover nearly their entire bodies with silver-colored paint, which often contains toxic compounds, including lead (Pb). The accumulation of lead in the body can disrupt inflammatory responses. This study aimed to investigate the correlation between blood lead concentration and C-Reactive Protein (CRP) levels in the serum of silver humans. This research employed an observational analytical design with a cross-sectional approach. The study variables included blood lead concentration as the independent variable and serum CRP levels as the dependent variable. The study population consisted of silver humans from the Purwokerto and Purbalingga regions. A total of 11 participants were selected using an accidental sampling technique. Blood lead levels were measured using atomic absorption spectrophotometry (AAS), while CRP levels were assessed qualitatively using the latex agglutination method. The results indicated no significant correlation between blood lead concentration and serum CRP levels in silver humans, as determined by the Fisher’s Exact Test (P-value = 0.491, P 0.05)